Effect of School Culture on Teachers’ Burnout and Job Performance at Elementary Level - Zulqarnain, Maryum; Ali, Vilayat; Bashir, Irfan (Pakistan Languages and Humanities Review, 2025)
This study aimed to explore the effect of school culture on teacher’s burnout and their job performance at the elementary school level in Lahore district using a causal-comparative design. The environment of an organization has a significant role in shaping the psychological well-being and performance of teachers. School culture is a major factor in improving teacher’s attitude, reducing the burnout rate, and enhancing their professional outcomes. However, limited research exits within the context of Pakistan, particularly at elementary level. The current quantitative study employed a causal-comparative design. Data were collected from 156 teachers serving at elementary school level using closed-ended questionnaires. The tool measured school culture, teacher’s burnout, and their job performance. In the study, convenience sampling strategy was used, and data were analyzed using SPSS, applying regression analysis and correlation coefficient to test hypothesis. Results showed that school culture significantly reduced teacher burnout and positively affected management skills and interpersonal relations of teachers. While no significant impact was found on their teaching skills or the overall job performance. The pearson correlation showed a negative association with discipline and regularity. In order to reduce burnout and strengthen performance, school leaders should foster inclusive, collaborative cultures. Further research should explore qualitative dimensions.